Parametric and modeling studies of Rhodamine-B adsorption using coconut coir-based materials as eco-friendly adsorbents. Issue 5 (October 2021) - Nascimento, Rogério J.M.; Pereira, Kilton Renan Alves; Avelino, Francisco
Abstract: The present study aimed to optimize the adsorption process of Rhodamine B (Rh-B) on crude and organosolv-based coconut fibers using a full factorial experimental design and response surface modeling. The modification of the fiber was carried out using an aqueous formic acid solution (85% wt.) at 100 ⁰C during 1 h. The crude and modified coconut fibers (CCF and MCF) were characterized regarding their chemical composition, water contact angle, scanning electron microscopy and X-ray diffraction and point of zero charge. The batch adsorption tests were performed to evaluate how the biosorbent dosage ([CCF] and [MCF]), contact time, temperature and initial concentration of Rh-B ([Rh-B]) would influence the removal efficiency of Rh-B and their adsorption capacity. Factorial designs of 3² type were carried out for each biosorbent. For the independent variables, the following levels were used: biosorbent concentration (2–4 g L −1 ), contact time (10–60 min), initial concentration of Rh-B (50–100 mg L −1 ) and temperature (298–318 K). The effects and interactions caused by the studied variables were statistically significant in the adsorption of Rh-B, based on the values obtained by the ANOVA test. The parameters that provided maximum adsorption of Rh-B onto CCF and MCF were 4 g L −1, 60 min, 318 K and 100 ppm, yielding qmax values of 13 mg g −1 and 22 mg g −1, respectively. The formosolv process enhanced the performance of coconut coir as biosorbent, while the parametric study was capable of optimizing and designing the parameters involved in Rh-B adsorption for both biosorbents. Graphical abstract: ga1